(untitled) (Research, Society and Development, 2020)
Goat milk may be an alternative to cow milk to people that suffer from allergic conditions, besides presenting high digestibility. Among dairy products, fermented milk is one of the most consumed. In this category, Kefir is a fermented milk that presents functional properties. Therefore, this laboratory research aimed to obtain Kefir from goat milk added by different guava pulp concentrations (0, 5, 15 and 25 %) and evaluate its physicochemical, microbiological and sensorial characteristics through quantitative data. Data obtained from microbiological analysis evidenced food safety for consumers and probiotic potential. The pulp concentration variation changed some physicochemical parameters. Sensorially, all the samples had high positive answer levels in the acceptance test, besides the last group had high percentage of buying intention. This study demonstrates that Kefir added with the higher guava pulp concentration presents potential to be introduced in the Brazilian market.